ANALISIS GAYA BAHASA IKLAN LAYANAN MASYARAKAT (ILM) TENTANG PANDEMI COVID-19 di YOUTUBE: LANGUAGE ANALYSIS OF COMMUNITY SERVICE ADS (PSAs) ABOUT COVID-19 PANDEMI on YOUTUBE - Rustang, Masita; Mayong; Sultan (Journal of Applied Linguistics and Literature, 2023)
This research is entitled Analysis of the language style of public service advertisements (PSAs) about the Covid-19 pandemic on YouTube. This research is a descriptive qualitative research that aims to describe the style of language contained in Public Service Advertisements (PSAs) related to the Covid-19 Pandemic on Youtube. The style of language examined in public service advertisements about the Covid-19 pandemic on YouTube totals eight advertisements. The results of the study regarding the use of language style in PSAs related to covid-19 found by researchers are 28 data which are divided into six personifications, five anaphora, one alliteration, two asindetons, seven polysyndetons, four hyperboles, two similes, and one metaphor